EcoDroneVerse: Pemantauan Sampah Sungai Berbasis AI-Drone dan Virtual Twin - Firmansyah; Masayu Sarah Amelia; Arabela Kogoya; Devani, Ferizka Tiara (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
River waste accumulation is one of the main causes of flooding in Indonesia. This study proposes the EcoDroneVerse concept, a river monitoring system using drones and artificial intelligence (AI) to create a virtual twin representing the real condition of rivers. The research employs a conceptual method including problem identification, literature review, concept formulation, and systematic analysis of potential technology application. The findings indicate that the system can detect waste both on the surface and below the water in real-time, map critical waste accumulation points, and simulate flood risk predictions. The integration of AI, drones, and virtual twin enables local governments to plan data-driven river cleaning actions and improve decision-making effectiveness in flood mitigation. Since the system is conceptual, prototype development and field testing are necessary for further validation. The proposed approach offers an innovative alternative for sustainable river management and flood control. Keywords—drone, artificial intelligence, virtual twin, river monitoring, flood mitigation